Robust determinants of OECD FDI in developing countries: Insights from Bayesian model averaging - Nikolaos Antonakakis; Gabriele Tondl (Cogent Economics & Finance, 2015)
In this paper, we examine the determinants of outward FDI from four major OECD investors, namely, the US, Germany, France, and the Netherlands, to 129 developing countries classified under five regions over the period 1995-2008. Our goal is to distinguish whether the motivation for FDI differs among these investors in developing countries. Rather than relying on specific theories of FDI determinants, we examine them all simultaneously by employing Bayesian model averaging (BMA). This approach permits us to select the most appropriate model (or combination of models) that governs FDI allocation and to distinguish robust FDI determinants. We find that no single theory governs the decision of OECD FDI in developing countries but a combination of theories. In particular, OECD investors search for destinations with whom they have established intensive trade relations and that offer a qualified labor force. Low wages and attractive tax rates are robust investment criteria too, and a considerable share of FDI is still resourcedriven. Overall, investors show fairly similar strategies in the five developing regions.
Keywords: C11; F0; F21; 330; FDI determinants; Bayesian model averaging; OECD; developing countries; the US; Germany; France; the Netherlands